Decolonising Australian doctoral education beyond/within the pandemic: Foregrounding Indigenous knowledges - Catherine Manathunga; Jing Qi; Maria Raciti; Kathryn Gilbey; Sue Stanton; Michael Singh (University of Johannesburg, 2022)
Global doctoral education has been particularly affected by the COVID-19 pandemic and the Black Lives Matter movement, which have drawn attention to the vast inequities faced by black, cultural minority and Indigenous peoples. These developments have focused urgent attention on the need to de-homogenise Australian doctoral education. Australian universities have been very slow to create recognition and accreditation programs for First Nations and transcultural (migrant, refugee and international candidates) knowledge systems, histories, geographies, languages and cultural practices in doctoral education. A significant body of research investigates Australian universities' education of Indigenous and transcultural doctoral candidates. However, few scholars have sought to trace the links between individual personal doctoral candidate life histories and large-scale Australian government policy trends. This paper draws upon the Indigenous knowledge global decolonization praxis framework and de Sousa Santos' theories about cognitive justice and epistemologies of the South to fill this gap. Future aspects of this project will involve conducting an international policy analysis, life histories and time mapping to implement key Indigenous knowledge approaches in Australian doctoral education. This paper will critically explore the application of three core First Nations knowledge approaches - the agency of Country, the power of Story and intergenerational, iterative and intercultural knowledges - to Australian doctoral education.